OPTIMAL STRUCTURE DESIGN AND TEST ANALYSIS OF PERMANENT MAGNETIC COUPLING FOR DYNAMIC SEALING - ZHU ZiNa; WU Peng; LAI LeiJie (Jixie qiangdu)
In order to achieve dynamic sealing in pressurized vessel considering non-leakage of harmful working medium,this study presents an optimal structure design of permanent magnetic coupling（ PMC）. For the optimization objective of increasing the torque transmission with limited magnetic material cost and decreasing the eddy-current loss of the magnetic coupling caused by the metal isolation cover,an improved partial swarm optimization method is designed to perform a multiobjective design optimization of the structure of PMC. After accurate computation,the optimal structure parameters of PMC are obtained. Then,a 3-D finite element model of PMC with the optimal structure is constructed to analyze the transmitted torque and eddy current loss,and an actual PMC device is manufactured for the non-leakage vessel application and the tested performance satisfies the technical demands,which provides theoretical reference for the PMC structural design in similar applications.